2006
DOI: 10.1590/s1516-31802006000200012
|View full text |Cite
|
Sign up to set email alerts
|

XmnI polymorphism is associated with fetal hemoglobin levels in hypoplastic syndromes

Abstract: CONTEXT AND OBJECTIVE: Acquired fetal hemoglobin (HbF) elevation has been implicated as a prognostic factor in dyserythropoietic disorders. Our objectives were to examine acquired HbF increases in aplastic anemia (AA) and paroxysmal nocturnal hemoglobinuria (PNH) patients, and to evaluate whether there is an association between the presence of XmnI and 5' hypersensitive site locus control region (LCR-HS2) polymorphisms and the HbF levels. DESIGN AND SETTING: Cross-sectional study at the Hematology and Blood Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…This heterogeneity is likely to be due to the presence of different β-thalassemia alleles or interaction with modulating genetic factors like associated α-thalassemia and/or a gene for raised HbF production (X mn 1 polymorphism) 23. Heterozygosity for presence of X mn 1 site polymorphism is also likely to influence phenotype24 and X mn 1 polymorphism absence reduction is associated with acquired HbF elevation 25. Gilmans13 data are consistent with the hypothesis that T at position - 1 58 causes the high HbF values.…”
Section: Discussionmentioning
confidence: 75%
“…This heterogeneity is likely to be due to the presence of different β-thalassemia alleles or interaction with modulating genetic factors like associated α-thalassemia and/or a gene for raised HbF production (X mn 1 polymorphism) 23. Heterozygosity for presence of X mn 1 site polymorphism is also likely to influence phenotype24 and X mn 1 polymorphism absence reduction is associated with acquired HbF elevation 25. Gilmans13 data are consistent with the hypothesis that T at position - 1 58 causes the high HbF values.…”
Section: Discussionmentioning
confidence: 75%
“…The XmnI polymorphism is a common genetic variation that was reported in previous studies to increase HbF level and therefore ameliorate the severity of the sickle cell disease.Our study shows that a polymorphism of the XmnI was found to be associated with higher expression of HbF in sickle cell and sickle cell trait patients. Several studies confirmed the association between XmnI and fetal hemoglobin 10,11 .Appositive association was observed between the HbF level and the presence of Xmn1 site in SS and sickle thalassemia groups Recently, other genetic association studies shown that several single nucleotide polymorphisms, associated with variation in the expression of HbF in sickle cell disease 12 .The XmnI polymorphism is known to influence the γ G gene expression in sickle cell anemia and to increased HbF concentrations when they are under conditions of erythropoietic stress 13 . Study conducted by FarizKahhaleh et.al to assist the Association of Xmn1 polymorphism and consanguineous marriage with fetal hemoglobin in Syrian patients with sickle cell disease they concluded that a strong evidence on the importance of Xmn1 polymorphism and consanguineous marriage, among other factors, in the prediction of clinical severity and hydroxyurea response in SCD patients 14 .…”
Section: Discussionmentioning
confidence: 86%

Association of XmnI Polymorphism with Fetal Hemoglobin Level in Sudanese Patients with Sickle Cell Disease

Tarig Osman Khalafallah Ahmed,
Abeer Alshazaly Abdulrahman Altag,
Ahmed Abdalla Agab Eldour
et al. 2021
IJOCM